Ukuvuyisana nabantu abadumileyo kumanqaku esiXhosa njengohlobo lokubhaliweyo - Ngcanga, Dorris Nosisa (Stellenbosch : Stellenbosch University, 2012)
This study has been undertaken to explore and investigate the genre-theoretic properties of social commentary texts in isiXhosa' -- P. ii.